2011
DOI: 10.1176/appi.ps.62.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sexual Orientation and Gender on Perceived Need for Treatment by Persons With and Without Mental Disorders

Abstract: Objective Research has shown that some individuals with sexual minority status have a higher prevalence of psychiatric disorders (both mental health and substance use) and also tend to seek treatment at higher rates as compared with similar heterosexuals. Relationships among treatment need and treatment use, however, are not well understood. This paper examines the relationship of sexual orientation and gender to perceptions of need and unmet need for treatment among individuals with and without mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Gender and sexual minority status were found to have a significant relationship with perceived treatment need in a secondary data analysis of a survey with a community-based single state probability sample (Grella et al, 2011). Among those who did not receive treatment during the prior year, women with mental disorders (mood, anxiety and/or substance use), regardless of sexual orientation, were more likely than men to perceive a need for treatment.…”
Section: Perceived Need For Treatmentmentioning
confidence: 96%
See 4 more Smart Citations
“…Gender and sexual minority status were found to have a significant relationship with perceived treatment need in a secondary data analysis of a survey with a community-based single state probability sample (Grella et al, 2011). Among those who did not receive treatment during the prior year, women with mental disorders (mood, anxiety and/or substance use), regardless of sexual orientation, were more likely than men to perceive a need for treatment.…”
Section: Perceived Need For Treatmentmentioning
confidence: 96%
“…A number of studies have sought to identify the predictors of perceived treatment need among community samples of individuals who meet criteria for SUDs (Grella, Cochran, Greenwell & Mays, 2011;Grella, Karno, Warda, Moore & Niv, 2009;Mojtabai et al, 2002;Tucker, Wenzel, Golinelli, Zhou & Green, 2011;Wu & Ringwalt, 2004), however, none have explicitly examined the moderating influence of gender on the relationship between substance use problem severity and perceived treatment need despite the fact that it has been suggested that gender impacts health and help seeking (Courtenay, 2000a). The purpose of the proposed study is to understand how gender impacts the relationship between substance use problem severity and perceived treatment need among a community sample of individuals who meet criteria for SUDs.…”
Section: The Purpose Of the Studymentioning
confidence: 99%
See 3 more Smart Citations